The Impact of Energy Price Volatility on Industrial Performance: A Review of Energy Efficiency and Renewable-Energy Adoption - Alief Muhammad; Mas Ahmad Baihaqi; Hartawan Abdillah; Tamam Asrori (Universitas Panca Marga, 2026)
The increasing volatility of global energy markets has created significant challenges for industrial sectors by increasing production costs, reducing competitiveness, and threatening operational stability. This study investigates how energy price volatility influences industrial performance and examines the roles of energy efficiency and renewable-energy adoption as adaptation mechanisms. A systematic literature review (SLR) was conducted based on 298 peer-reviewed articles published between 2020 and 2026 from Scopus, Web of Science, ScienceDirect, and Google Scholar. The selected studies were analyzed using thematic synthesis to identify major research trends, causal mechanisms, and emerging research gaps. The findings reveal that energy price volatility represents a critical external shock affecting industrial performance through increased operational costs, supply-chain disruption, investment uncertainty, and reduced competitiveness. However, the literature also demonstrates that firms can reduce vulnerability through internal adaptation capabilities. Energy efficiency functions as a strategic capability by reducing energy intensity, improving operational flexibility, and mitigating cost pressures, while renewable-energy adoption provides a buffering mechanism by diversifying energy sources and reducing dependence on volatile fossil-fuel markets. The review integrates Resource Dependence Theory, Resource-Based View, Dynamic Capability Theory, and Natural Resource-Based View to explain how industrial firms transform energy uncertainty into resilience capabilities. The study highlights that future industrial competitiveness will depend not only on access to affordable energy but also on firms’ ability to develop adaptive energy strategies, digital energy-management capabilities, and sustainable energy systems. This review provides a conceptual foundation for understanding industrial resilience under increasing global energy uncertainty.